Social ties, prior experience, and venture creation by transnational entrepreneurs. (2019) - Pruthi, Sarika; Wright, Mike
The interaction between resources, and host and home country contexts of transnational entrepreneurs (TEs), is important for understanding their strategies and hence performance of their ventures. Yet, how they deploy their unique experiences and social networks in the founding of ventures in multiple institutional contexts is less understood. Based on 15 in-depth interviews with TEs of Indian origin in the UK, and nine of their counterpart heads of transnational venture (TNV) operations, we explore the use of prior experience, and personal and industry ties in the founding of TNVs in their home country. Our findings show that the way TEs use personal and industry ties in the host and home countries is contingent on whether they have prior experience of: 1) entering the home country; 2) implementing the business opportunity underlying the TNV in the home country, respectively, with a former employer. The implications of these findings are discussed.